The Determinant Factors of the Intention to spend more time binge-watching for Netflix Subscriber in Jakarta - Susanno, Rebecca; Phedra, Ryan; Murwani, Ina Agustini (Journal of Research in Marketing (ISSN: 2292-9355), 2019)
In the advancement of technology and entertainment industry, Video-on-Demand (VOD) allows viewers to watch anything, anytime, anywhere. These platforms stimulate the intention to Binge-Watch. By analyzing the pattern of binge-watching and the effect it brings to Netflix, this study aims to figure out if it has an effect on consumer loyalty. The purpose of the study is to explore the pre-binge intentions and outcomes that influence Jakarta millennials to spend more time binge-watching especially for Netflix subscriber. This study used a quantitative research method with online questionnaire. There are 3 criteria the respondents have to meet: 1) Millennials, 2) Live in Jakarta, 3) Active Netflix subscribers. The research method is convenience sampling by using online form, with 32 Questions and five-point Likert scale. For the data analysis, SPSS was used to test the reliability and validity of the data. The key findings are: (a) Majority of millennials that live in Jakarta are active Millennials subscribers, (b) The three factors that motivate millennials to binge-watch are; Escape, Social engagement, and Attractive price. The findings are quite different from the original study because Indonesian people tend to be more price sensitive. The limitations of current study suggestions for future researches are listed.